The Cruise control diet : automate your diet and conquer weight loss forever - Cruise, Jorge (Ballantine Books, 2019)
"Activate your weight-loss autopilot--use the power of simple on/off fasting to lose the pounds and keep them off, from Hollywood trainer and #1 New York Times bestselling author Jorge Cruise. Timing is everything when it comes to losing weight. Or, as celebrity trainer Jorge Cruise explains: When we eat is as important as what we eat. Building on the scientifically proven but hard-to-sustain day-on, day-off technique known as "intermittent fasting," Cruise has developed a revolutionary masterplan that simplifies your calendar and eliminates between-meal hunger. He divides every day into two easy-to-remember nutritional zones: a 16-hour evening and overnight "burn zone" (semi-fasting) followed by an 8-hour "boost zone" (eating). Ingeniously, his plan also includes "bumper foods" that can be consumed in either zone--around the clock--to keep you satiated and burning fat throughout. You'll never be hungry if you don't really ever have to fully fast! Backed by the very latest research and client-tested for optimal results, The Cruise Control Diet unlocks the key to dramatic results with 50 recipes for deliciously unexpected boost zone foods, such as Margherita Pizza, Spaghetti Squash Lasagna, Turmeric Shrimp, and even Chocolate Chunk Cookies. 15 high-fat, no-sugar burn-zone recipes for craving-quenching foods like Chocolate Coconut Mousse and Caramel Chai Latte weekly menus and handy grocery lists to take the guess work out of the equation candid testimonials from Cruise's clients and test-panel participants an optional burn-zone exercise program with instructional photos. With The Cruise Control Diet you'll automate your diet and finally conquer weight loss forever!"--